Learning by Developing in Higher Education - Raij, Katariina (Neveléstudomány | Oktatás – Kutatás – Innováció, 2013)
This article describes the Learning by Developing (LbD) action model developed to meet the future challenges. It takes into account the new role of higher education institutes in a world where changes are continuous and today’s truth is not competent tomorrow. The article discusses the new ways of ‘teaching’ by inviting to move from a knower’s world to a competent actor’s world. It further attempts to rediscover a pragmatic learning theory as a basis for the development of higher education. The article describes the development of LbD by following the changes in the nature of higher education guided by the expectations of the surrounding world. It begins with a competence – oriented approach and concludes by intruducing the LbD action model that integrates competence – producing learning and an innovative research and development project.